The Anxiety Caused by Secondary Schools for Autistic Adolescents: In Their Own Words - Debra Costley (MDPI AG, 2021)
Secondary schools are increasingly becoming inclusive of all students whatever their individual needs, but we question whether teachers understand enough about specific needs in order to effectively support all their students. Research indicates that autistic students often struggle with aspects of school (conformity; social communication; sensory challenges; bullying) but very few studies ask autistic adolescents about their experiences. One of the key elements of the school experience for autistic adolescents is the levels of anxiety experienced by many students on a daily basis. This research set out to explore the extent to which autistic students in secondary schools in the UK were able to recognise and reflect on their own anxiety. The eighteen participants in this co-produced qualitative study took part in semi-structured interviews planned by a team of autistic and non-autistic researchers. The themes that emerged from this study, in terms of triggers for anxiety, included other people’s behaviour, fear of the unknown, and sensory sensitivities. A theoretical view of their difficulties concurs with the concept of intolerance of uncertainty. Our data suggest that autistic students continue to experience high levels of anxiety throughout their secondary education, despite supports put in place by some schools. Strategies are highlighted that could be implemented by all schools to promote truly inclusive settings.